Deliberation and polarization: a multi-disciplinary review - Caluwaerts, Didier; Bernaerts, Kamil; Kesberg, Rebekka; Smets, Lien; Spruyt, Bram (Frontiers in Political Science, 2023)
In recent years, deliberative democracy has drawn attention as a potential way of fighting polarization. Allowing citizens to exchange arguments and viewpoints on political issues in group, can have strong conflict-mitigating effects: it can foster opinion changes (thereby overcoming idea-based polarization), and improve relations between diametrically opposed groups (thereby tackling affective forms of polarization, such as affective polarization). However, these results conflict with social psychological and communication studies which find that communicative encounters between groups can lead to further polarization and even group think. The question therefore arises under which conditions deliberative interactions between citizens can decrease polarization. Based on a multidisciplinary systematic review of the literature, which includes a wide diversity of communicative encounters ranging from short classroom discussions to multi-weekend citizen assemblies, this paper reports several findings. First, we argue that the effects of communicative encounters on polarization are conditional on how those types of communication were conceptualized across disciplines. More precisely, we find depolarizing effects when group discussions adhere to a deliberative democracy framework, and polarizing effects when they do not. Additionally, we find that the depolarizing effects depend on several design factors that are often implemented in deliberative democracy studies. Finally, our analysis shows that that much more work needs to be done to unravel and test the exact causal mechanism underlying the polarization-reducing effects of deliberation. Many potential causal mechanisms were identified, but few studies were able to adjudicate how deliberation affects polarization.